What Magdalena Said - Stewart, Michael (BBC, 1993)
'I want to become a public prosecutor to clean my town of all the brown-skinned inhabitants''- the words of Magdalena Babicka, runner-up at the 1993 Miss Czech-Slovak contest. The film goes to Magdalena's town to explore the world which made Magdalena, juxtaposing the experience of Czech Rom, in danger of losing their homes and citizenship. Film about the persecution of Gypsies in the post-Communist Czech Republic.